Transcriptional and functional remodeling of lung-resident T cells and macrophages by Simian varicella virus infection - Doratt, Brianna M.; Malherbe, Delphine C.; Messaoudi, Ilhem (Frontiers in Immunology, 2024)
Varicella zoster virus (VZV) causes varicella and can reactivate as herpes zoster, both diseases present a significant burden worldwide. However, the mechanisms by which VZV establishes latency in sensory ganglia and disseminates to these sites remain unclear. Here, we combined a single cell sequencing approach and a well-established rhesus macaque experimental model using Simian varicella virus (SVV), which recapitulates the VZV infection in humans, to define the acute immune response to SVV in the lung as well as compare the transcriptome of infected and bystander lung-resident T cells and macrophages. Our analysis showed a decrease in frequency of alveolar macrophages concomitant with an increase in that of infiltrating macrophages expressing antiviral genes as well as proliferating T cells, effector CD8 T cells, and T cells expressing granzyme A (GZMA) shortly after infection. Moreover, infected T cells harbored higher numbers of viral transcripts compared to infected macrophages. Furthermore, genes associated with cellular metabolism (glycolysis and oxidative phosphorylation) showed differential expression, in infected cells suggesting adaptations to support viral replication. Overall, these data suggest that SVV infection remodels the transcriptome of bystander and infected lung-resident T cells and macrophages.